Analisa Proteksi Arus Lebih Gangguan Tanah Pada Feeder Gardu Induk Garuda Sakti - Grace Arisantha; Edy Hamdani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
There are a lot of disruption in the distribution of electrical energy which can result in interruption of the power supply to the load. It is necessary for the protection or security system that is reliable to anticipate when an interruption occurs. Protection system serves to separate the problematic parts with which is not for the system to remain operational.Usually 20 KV feeder outages caused by short circuit. Total blackout (black out) can occur when setting the relay or in this study were discussed Ground Fault Relay (GFR) on the incoming or outgoing unfavorable. For that one effort that can be done is to analyze the protection relay settings, so that mutually coordinated well and is expected if an interruption in one of the feeder it will not make black out the other.From the research, the high short-circuit fault current is influenced by the distance of the point of interruption, the greater the distance the point of interruption, the smaller the short circuit fault current and vice versa. Where it is known from the analysis set Ground Fault Relay (GFR) at 20 KV incoming side has a delay of work, so do resetting on the incoming side by setting the delay time becomes 0.28 seconds.Keywords : Ground Fault Relay, short circuit, one phase to ground